2010
DOI: 10.1002/cncr.25462
|View full text |Cite
|
Sign up to set email alerts
|

A phase 2 trial of single‐agent bevacizumab given in an every‐3‐week schedule for patients with recurrent high‐grade gliomas

Abstract: BACKGROUND:The authors evaluated a 3-week schedule of bevacizumab in patients with recurrent high-grade glioma (HGG). METHODS: Patients received bevacizumab 15 mg/kg every 3 weeks and were evaluated every 6 weeks until tumor progression. Tissue correlates were used to quantify tumor content of vascular endothelial growth factor A (VEGFA) and vascular endothelial growth factor receptor-2 (VEGFR2). RESULTS: Of 61 patients who were treated (35 men and 26 women; median age, 52 years; age range, 21-78 years), 50 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
79
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 139 publications
(86 citation statements)
references
References 46 publications
(95 reference statements)
6
79
1
Order By: Relevance
“…In fact, median os achieved in the B1L group was 13 months (95% ci: 10.0 to 26.0 months); in the B2L+ group, it was 7 months (95% ci: 3.2 to 8.0 months). Our results suggest that the use of bevacizumab in a second-line setting accords with the registration data for recurrent gbm [14][15][16][17][18][19][20][21][22] and should remain the current standard.…”
Section: Discussionsupporting
confidence: 66%
“…In fact, median os achieved in the B1L group was 13 months (95% ci: 10.0 to 26.0 months); in the B2L+ group, it was 7 months (95% ci: 3.2 to 8.0 months). Our results suggest that the use of bevacizumab in a second-line setting accords with the registration data for recurrent gbm [14][15][16][17][18][19][20][21][22] and should remain the current standard.…”
Section: Discussionsupporting
confidence: 66%
“…In Europe, approval was refused because of the lack of a bevacizumab-free control arm. There are 9 phase II trials with a bevacizumab monotherapy arm, 3 of them single-arm studies [86][87][88], 5 trials compared bevacizumab with bevacizumab plus another agent, such as irinotecan [85], carboplatin [84], the histone-deacetylase inhibitor vorinostat [89], the multikinase inhibitor dasatinib [90] or lomustine [58]. Only one trial had a bevacizumab-free control arm with lomustine [54].…”
Section: Other Classical Non-alkylating Chemotherapymentioning
confidence: 99%
“…Only one trial had a bevacizumab-free control arm with lomustine [54]. Most of these trials used bevacizumab at 10 mg/kg IV every 2 weeks except one study with 15 mg/kg IV every 3 weeks [87] and one study with 5 mg/kg IV every 3 weeks when combined with lomustine [58]. Toxicity of bevacizumab was mainly non-hematologic including hypertension, thrombembolic events, fatigue, and impaired wound healing.…”
Section: Other Classical Non-alkylating Chemotherapymentioning
confidence: 99%
“…35,36 Bevacizumab-Based Regimens in Patients With Recurrent Glioblastoma Multiple subsequent studies have been reported since provisional FDA approval, seeking to better define outcomes for bevacizumab, as well as to improve on them with alternative chemotherapy combinations. A prospective phase 2 study using every-3-week dosing of bevacizumab at a dose of 15 mg/kg in 61 patients with World Health Organization grade 3 or grade 4 glioma demonstrated no obvious differences in patient outcomes compared with contemporary studies using every-2-week dosing at 10 mg/kg, 37 thus allowing for flexibility in patient scheduling without clinical detriment. Several phase 2 trials of bevacizumab-based combinations have also been reported for recurrent glioblastoma (Table 1), 27,28,32, including bevacizumab with irinotecan, irinotecan plus cetuximab, irinotecan plus carboplatin, etoposide, fotemustine, sorafenib, temozolomide, erlotinib, and temsirolimus.…”
Section: Early Study Of Bevacizumab In Patients With Recurrent Glioblmentioning
confidence: 96%